Zukunft der Arbeit in Industrie 4.0 - Botthof, Alfons; Hartmann, Ernst Andreas (Springer Nature, 2015)
Industrial and Production Engineering; Robotics and Automation; Engineering Economics, Organization, Logistics, Marketing; Manufacturing, Machines, Tools; Information Systems Applications (incl. Internet)